118k views
0 votes
How do you solve this problem in the photo?

How do you solve this problem in the photo?-example-1
User Alex North
by
5.2k points

2 Answers

0 votes

Answer:

25

Explanation:

Using the rule of exponents


a^(m) ×
a^(n)
a^((m+n))

The rule can be extended to include more than 3 terms.

Given

5³ ×
5^(4) ×
5^(-5)

=
5^((3+4-5))

= 5²

= 25

4 votes

Answer: 5^2

Explanation:

Since the base are all the same, you will add the exponents and let the exponents stay the same.

5^3 * 5^4= 5^7 * 5^-5= 5^2

User NameOfTheRose
by
5.3k points